Nexo de causalidade: o art. 13 do CP e a teoria da imputação objetiva - Lima, André Estefam Araújo (2008)
This work examines the relation of causality through the theory of objective imputation, searching to verify under different approaches, which is the ideal criterion to attribute a normative result to a criminally relevant behavior. It was taken care of to discourse on the function of the Criminal law (under the optics of the doctrine and the Brazilian legislation) for, from then on, meeting the bases on which it intends to construct a correct theory of the imputation. It was analyzed the evolution of the criminal systems, since the classic until the funcionalist , in order to verify the approach that it was given, through them, to the causal nexus. The central argument of the work consists of firming position in the direction of that the causality nexus cannot be considered under an exclusively natural approach, otherwise it is to become the Criminal law into an appendix of Natural Sciences. In order to achieve this, it is necessary, in first place, to define in which system should the structure of the crime anchor. It must, then, be considered the existing peculiarities in our legal system, which contains the nexus of causality in the Criminal Code (art. 13). From these premises, this study considers a harmonization between the material relation of causality, as stated on the Code, and the theory of the objective imputation, as an adequate factor to restrict decurrent injustices of the rule foreseen in the Legal Text